Impacts of the Belt and Road Initiative on regional outward FDI from China based on evidence from 2000 to 2015 - Yuanyuan Li (ZFW - Advances in Economic Geography, 2023)
Firms from different provinces in China and their different reactions to the Belt and Road Initiative (BRI) are studied in this research. Initial results from 27.547 outward foreign direct investment (FDI) projects by Chinese firms between 2000 and 2015 regarding the home region profile, host country choice, and FDI motives of the investment firms before and in the early years of the launch of the BRI policy are investigated. The findings show that Chinese firms from eastern provinces that have accumulated a large quantity of inward FDI are more likely than firms from western provinces to switch their investments to BRI-involved countries and engage in a more diverse set of outward FDI motives. These findings help interpret the behavior of Chinese multinationals in the current (de)globalization era, namely using the BRI to circumvent FDI barriers imposed by advanced western economies.
Keywords: 330; (de)globalization; Belt and Road Initiative (BRI); FDI motives; Foreign Direct Investment (FDI); Location Choices